Microscopy and spectroscopy approaches to study GPCR structure and function - Fessl, Tomáš; Majellaro, Maria; Bondar, Alexey (British journal of pharmacology, 2025)
The GPCR signalling cascade is a key pathway responsible for the signal transduction of a multitude of physical and chemical stimuli, including light, odorants, neurotransmitters and hormones. Understanding the structural and functional properties of the GPCR cascade requires direct observation of signalling processes in high spatial and temporal resolution, with minimal perturbation to endogenous systems. Optical microscopy and spectroscopy techniques are uniquely suited to this purpose because they excel at multiple spatial and temporal scales and can be used in living objects. Here, we review recent developments in microscopy and spectroscopy technologies which enable new insights into GPCR signalling. We focus on advanced techniques with high spatial and temporal resolution, single-molecule methods, labelling strategies and approaches suitable for endogenous systems and large living objects. This review aims to assist researchers in choosing appropriate microscopy and spectroscopy approaches for a variety of applications in the study of cellular signalling. LINKED ARTICLES: This article is part of a themed issue Complexity of GPCR Modulation and Signaling (ERNST). To view the other articles in this section visit http://onlinelibrary.wiley.com/doi/10.1111/bph.v182.14/issuetoc.
Keywords: Receptors, G-Protein-Coupled; Animals; Signal Transduction; receptory spřažené s G-proteiny; lidé; spektrální analýza; zvířata; mikroskopie; signální transdukce; Microscopy; Spectrum Analysis; Humans